Drug interactions of opioid analgesics – weak opioids - Kotlińska-Lemieszek, Aleksandra (Medycyna Paliatywna/Palliative Medicine, 2011)
Drugs used in a patient create a net of complex relations. These agents modify their effect in multiple mechanisms, including acting at the same receptor, enzyme or effector, as well as affecting all phases of pharmacokinetics, from absorption to elimination. The knowledge on this issue is still fragmentary, based on experimental in vitro studies, surveys on volunteers, very few clinical studies and single case reports. The article comprises the review of the literature on interactions of the second step of WHO analgesic ladder opioids.